2020
DOI: 10.3389/fpsyg.2020.582054
|View full text |Cite
|
Sign up to set email alerts
|

Out of Control – Privacy Calculus and the Effect of Perceived Control and Moral Considerations on the Usage of IoT Healthcare Devices

Abstract: People are increasingly applying Internet of Things (IoT) devices that help them improve their fitness and provide information about their state of health. Although the acceptance of healthcare devices is increasing throughout the general population, IoT gadgets are reliant on sensitive user data in order to provide full functioning and customized operation. More than in other areas of IoT, healthcare applications pose a challenge to individual privacy. In this study, we examine whether actual and perceived co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 75 publications
1
31
0
1
Order By: Relevance
“…The privacy calculus (Culnan & Armstrong, 1999) assumes that people weigh the anticipated privacy costs and benefits before they decide to disclose personal information (Dienlin & Metzger, 2016), install an app (Eling et al, 2013), or adopt new technology (Princi & Krämer, 2020). For instance, perceived privacy costs (e.g., privacy threats) have been found to negatively affect online self-disclosure (Bol et al, 2018) or the likelihood to install an app (Eling et al, 2013).…”
Section: Privacy Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…The privacy calculus (Culnan & Armstrong, 1999) assumes that people weigh the anticipated privacy costs and benefits before they decide to disclose personal information (Dienlin & Metzger, 2016), install an app (Eling et al, 2013), or adopt new technology (Princi & Krämer, 2020). For instance, perceived privacy costs (e.g., privacy threats) have been found to negatively affect online self-disclosure (Bol et al, 2018) or the likelihood to install an app (Eling et al, 2013).…”
Section: Privacy Calculusmentioning
confidence: 99%
“…Several studies found that the anticipation of social benefits increases the likelihood of information disclosure on social networking sites (SNSs; Krasnova et al, 2010) or that the perception of convenience increases likelihood of smart technology adoption (Zheng et al, 2018). Frequently, benefit perceptions are found to be the driving factor of self-disclosure or technology adoption (e.g., Dienlin & Metzger, 2016;Krasnova et al, 2014;Princi & Krämer, 2020). One explanation for this observation can be found in the gratification hypothesis that assumes the expected benefits to outweigh the perceived risks, for instance, because people overrate the gratifications or because they are unaware of the privacy threats (Trepte et al, 2015).…”
Section: The Influence Of Benefitsmentioning
confidence: 99%
“…Yakın tarihli çalışmalar incelendiğinde ise sağlık hizmetlerinde sensör bulutunda anormalliğin algılanması (Kumar Dwivedi, Kumar, & Buyya, 2021), IoT tabanlı sağlık hizmetlerinde reçete analizi gibi uygulamalar için kelime benzerliği ölçüm yöntemi (Zhang vd., 2021), IoT tabanlı akıllı hastanelerde tasarımı etkileyen faktörlerin analizi (Uslu, Çalış, Okay, & Dursun, 2020), solunum hastalıklarında sağlık hizmeti internetinin tasarımı ve uygulanması (Tsai vd., 2020), klinik deneylerin iyileştirilmesinde ileri teknolojilerin uygulanmasına yönelik sistematik haritalama (Ngayua, He, & Boahene, 2020), hastalığın erken teşhisi için güvenli uzaktan sağlık izleme modeli (Akhbarifar, Javadi, Rahmani, & Hosseinzadeh, 2020), kontrol edilemeyen gizlilik hesaplamalarının algılanan kontrol ve ahlaki hususların IoT tabanlı sağlık cihazlarının kullanımına etkisi (Princi & Kramer, 2020), IoT'nin sağlık hizmetlerinde kullanımının etkisi ve sonuçları (Kelly, Campbell, & Scuffham, 2020), doktorların Covid-19 salgını sırasında Irak'ta iot tabanlı ağlık cihazlarını kullanma niyetlerinin incelenmesi (Alhasan vd., 2020), C-ortalamalar algoritması kullanılarak sağlık hizmetlerinde büyük verilerin kümelenmesi (Purandhar, Ayyasamy, & Saravanakumar, 2020) konularının araştırıldığı sonucuna varılmıştır. Konular göz önünde bulundurulduğunda ayrıntıların ele alınmaya başlandığı görülmektedir.…”
Section: Discussionunclassified
“…The technology acceptance model (TAM) is the most frequently adopted theory in explaining technology usage (Princi and Krämer, 2020). Due to the simple construction of TAM, it has been widely adopted to investigate users' acceptance of different kinds of technologies.…”
Section: Theory Of the Technology Acceptance Modelmentioning
confidence: 99%